127 Comparison of long-term progestin-based protocols to synchronize estrus prior to fixed-time artificial insemination or natural service in Bos indicus-influenced beef heifers. (7th December 2018) - Locke, J; Thomas, J; Knickmeyer, E; Ellersieck, M; Yelich, J; Poock, S; Smith, M; Patterson, D
Abstract: An experiment was designed to evaluate reproductive performance of Bos indicus-influenced beef heifers (n=1, 456). Weights and reproductive tract scores (RTS; Scale 1–5) were obtained prior to assignment of one of five treatments: Non-synchronized+natural service (NS); melengestrol acetate+NS (MGA+NS; 0.5 mg∙animal2α (PG; 25 mg, IM) 16 or 19d following CIDR or MGA removal. Fixed-time AI was performed 66 and 72h after PG for CIDR-PG and MGA-PG treatments, respectively. Gonadotropin-releasing hormone (GnRH; 100μg, i.m.) was administered at FTAI. Heifers in FTAI treatments were exposed to fertile bulls 12d after FTAI. Blood samples were collected and ovarian ultrasounds performed at PG administration and FTAI to compare serum concentrations of estradiol and progesterone and evaluate follicular dynamics among a subset of FTAI-assigned heifers. Pregnancy status was determined after the 65-d breeding period. Mean estradiol concentrations at AI differed between MGA- versus CIDR-treated heifers (P=0.04; 8.2 versus 6.6 pg/ml). Estrous response (52% versus 53%) and FTAI pregnancy rates (40%) did not differ between MGA- and CIDR-PG treatments, respectively. Pregnancy rates were compared at 21 and 60d of the breeding period based on pubertal status (prepubertal: RTS=1–2; peripubertal: RTS=3; pubertal: RTS=4–5). Pregnancy rates differed based on pubertal status (P≤0.02) and weight (P≤0.05). No differences presented with regard to progestin source, although higher pregnancy rates (P≤0.004) were observed among NS treatments than among FTAI followed by NS exposure at 60d. These data emphasize the importance of early attainment of puberty in Bos indicus-influenced beef heifers and provide a rationale regarding the need for improvements in reproductive management of this biological type.